2019
DOI: 10.1242/bio.046524
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic reticulum stress-induced cellular dysfunction and cell death in insulin-producing cells results in diabetes-like phenotypes in Drosophila

Abstract: The destruction of pancreatic β cells leads to reduced insulin secretion and eventually causes diabetes. Various types of cellular stress are thought to be involved in destruction and/or malfunction of these cells. We show that endoplasmic reticulum (ER) stress accumulation in insulin-producing cells (IPCs) generated diabeteslike phenotypes in Drosophila. To promote the accumulation of extra ER stress, we induced a dominant-negative form of a Drosophila ER chaperone protein (Hsc70-3 DN) and demonstrate that it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 60 publications
(85 reference statements)
0
24
0
Order By: Relevance
“…Activation of the Drosophila ER chaperone protein Hsc70‐3 DN resulted in a decrease in the number of IPCs due to the induction of apoptosis. It has also been shown that the relative expression levels of dilp2 , dilp3 , and dilp5 are significantly reduced in flies expressing the dominant negative form of Hsc70‐3 (Katsube et al, 2019).…”
Section: Factors Affecting Transcription Of Dilpsmentioning
confidence: 99%
“…Activation of the Drosophila ER chaperone protein Hsc70‐3 DN resulted in a decrease in the number of IPCs due to the induction of apoptosis. It has also been shown that the relative expression levels of dilp2 , dilp3 , and dilp5 are significantly reduced in flies expressing the dominant negative form of Hsc70‐3 (Katsube et al, 2019).…”
Section: Factors Affecting Transcription Of Dilpsmentioning
confidence: 99%
“…Furthermore, Hsc70‐3 acts as an endoplasmic reticulum (ER) chaperone, similar to its mammalian ortholog, GRP78 (Daugaard et al., 2007). A recent study has revealed that the ectopic expression of a dominant negative form of the protein activates the ER stress‐induced unfolded protein response (Katsube et al., 2019). Such reports strengthen our hypothesis that the cell growth defects of Hsc70‐3‐ silenced spermatocytes might be attributed to the inhibition of protein synthesis due to ER stress.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, genes encoding the Hsc70 group of proteins show high levels of expression in both testes and ovaries in Drosophila , suggesting their roles in gametogenesis in Drosophila (see Flybase, http://flybase.org/). These proteins may contribute to the folding of proteins synthesized de novo and maintain the tertiary structures of proteins under conditions of stress (Bukau & Horwich, 1998; Katsube et al., 2019; Ryoo & Steller, 2007). One of the members of the Hsc70 family, Hsc70‐4, is required for the self‐renewal of germline stem cells and differentiation of daughter cells in Drosophila (Yu et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…This resulted in increased glucose levels and reduced DILP expression. Using this model, authors demonstrated that diabetes onset might be triggered by a cause–effect relationship between ER stress and induced destruction of IPCs mediated by apoptosis [ 121 ].…”
Section: Drosophila As a Diabetes Modelmentioning
confidence: 99%